2008
DOI: 10.1007/s00595-008-3798-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in laboratory values and their relationship with time after rupture of an abdominal aortic aneurysm

Abstract: Both survivors and nonsurvivors of RAAA surgery displayed characteristic time-dependent laboratory abnormalities. Awareness of these responses may help us predict patients prone to complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
1
7
2
Order By: Relevance
“…Recently, several epidemiological studies have shown that a higher serum GGT level, even within the normal range, is associated with cardiovascular risk factors such as hypertension, hypertriglyceridemia, obesity, type 2 diabetes mellitus and stroke, as well as certain types of cancer 210 . In contrast to these studies, we observed that after surgery for ruptured abdominal aortic aneurysm 11 or after liver resection 12 , GGT is transiently increased in patients who had a good outcome. In these short-term observational studies GGT level was inversely related to other liver laboratory parameters such as aspartate aminotransferase (ALT), alanine aminotransferase (AST) as well as total bilirubin (TBI) 11, 12 .…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Recently, several epidemiological studies have shown that a higher serum GGT level, even within the normal range, is associated with cardiovascular risk factors such as hypertension, hypertriglyceridemia, obesity, type 2 diabetes mellitus and stroke, as well as certain types of cancer 210 . In contrast to these studies, we observed that after surgery for ruptured abdominal aortic aneurysm 11 or after liver resection 12 , GGT is transiently increased in patients who had a good outcome. In these short-term observational studies GGT level was inversely related to other liver laboratory parameters such as aspartate aminotransferase (ALT), alanine aminotransferase (AST) as well as total bilirubin (TBI) 11, 12 .…”
Section: Introductioncontrasting
confidence: 99%
“…In contrast to these studies, we observed that after surgery for ruptured abdominal aortic aneurysm 11 or after liver resection 12 , GGT is transiently increased in patients who had a good outcome. In these short-term observational studies GGT level was inversely related to other liver laboratory parameters such as aspartate aminotransferase (ALT), alanine aminotransferase (AST) as well as total bilirubin (TBI) 11, 12 . We observe that in the early postoperative period after a liver transplantation (LT) a transient gradual increase in GGT also occurs.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Likewise, in patients with liver disease, elevated GGT is considered a marker of cholestasis together with indicators such as bilirubin and alkaline phosphatase. We observed earlier that secondarily elevated GGT was associated with increased survival rates after liver transplantation, liver resection and after surgical repair of a ruptured abdominal aortic aneurysm [28][29][30]. The current observation in a large cohort of critically ill patients as well as in patients with prolonged ICU stay (SMF §12.1) or in subgroups without known primary liver disease (e.g.…”
Section: Discussionmentioning
confidence: 54%